Health impacts from cyanobacteria harmful algae blooms: Implications for the North American Great Lakes - Carmichael, Wayne W.; Boyer, Gregory L. (Harmful algae, 2016)
Harmful cyanobacterial blooms (cHABs) have significant socioeconomic and ecological costs, which impact drinking water, fisheries, agriculture, tourism, real estate, water quality, food web resilience and habitats, and contribute to anoxia and fish kills. Many of these costs are well described, but in fact are largely unmeasured. Worldwide cHABs can produce toxins (cyanotoxins), which cause acute or chronic health effects in mammals (including humans) and other organisms. There are few attempts to characterize the full health-related effects other than acute incidences, which may go unrecorded. At present these are difficult to access and evaluate and may be ascribed to other causes. Such information is fundamental to measure the full costs of cHABs and inform the need for often-costly management and remediation. This paper synthesizes information on cHABs occurrence, toxicology and health effects, and relates this to past and current conditions in the Great Lakes, a major global resource which supplies 84% of the surface water in North America. This geographic region has seen a significant resurgence of cHABs since the 1980s. In particular we focus on Lake Erie, where increased reporting of cHABs has occurred from the early 1990's. We evaluate available information and case reports of cHAB-related illness and death and show that cHABs occur throughout the basin, with reports of animal illness and death, especially dogs and livestock. Lake Erie has consistently experienced cHABs and cyanotoxins in the last decade with probable cases of human illness, while the other Great Lakes show intermittent cHABs and toxins, but no confirmed reports on illness or toxicity. The dominant toxigenic cyanobacterium is the genus Microcystis known to produce microcystins. The presence of other cyanotoxins (anatoxin-a, paralytic shellfish toxins) implicates other toxigenic cyanobacteria such as Anabaena (Dolichospermum) and Lyngbya.